Partisipasi Anggaran dan Orientasi Tujuan Sistem Organisasi sebagai Variabel Moderating dalam Hubungan antara Orientasi Profesional dan Konflik Peran pada Rumah Sakit Di Prop. Bengkulu - Isma Coryanata (Universitas Muhammadiyah Yogyakarta, Indonesia, 2006)
This research is aimed to examined empirically whether budget participation and orientation of organizational goal system as the moderating variables influence the relation between professional orientation and role conflict on hospitals in Bengkulu. Directly questionnaires were distributed to 50 managers from hospitals in Bengkulu by purposive sampling . The responses from 36 managers ( 72,9%) were analyzed by using regression analysis. The result indicated that budget participation as a moderating variable did not affecte the relation between professional orientation and role conflict but organizational goal system as a moderating variable affected the relation between professional orientation and role conflict.